2020
DOI: 10.17485/ijst/v13i42.1664
|View full text |Cite
|
Sign up to set email alerts
|

A study of parent’s opinion on online teaching in Delhi-NCR schools

Abstract: Objectives: To explore the challenges parents face when their children study online. Their views and opinions on the efficacy of the online learning program and the attributes of virtual classes are sought in the study. Methods: A survey study was conducted with an online questionnaire administered to more than 2000 parents of pre primary and primary classes from ten public schools of Delhi National Capital Region. Findings: More than 75% of the parents surveyed are satisfied with the online classes taking pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…This paper expands the personalized recommendation list, uses knowledge pictures to judge students' long-term preferences, and constructs a mixed knowledge map through feedback model and students' interest offset model to judge some time-sensitive factors such as the content change of online political and ideological education resources and the fluctuation of students' preferences [ 19 , 20 ].…”
Section: Personalized Recommendation Methods Of Online Political and ...mentioning
confidence: 99%
“…This paper expands the personalized recommendation list, uses knowledge pictures to judge students' long-term preferences, and constructs a mixed knowledge map through feedback model and students' interest offset model to judge some time-sensitive factors such as the content change of online political and ideological education resources and the fluctuation of students' preferences [ 19 , 20 ].…”
Section: Personalized Recommendation Methods Of Online Political and ...mentioning
confidence: 99%
“…Berdasarkan hasil temuan dan analisis didapat simpulan bahwa kunci keberhasilan pembelajaran daring tidak hanya dibebankan pada orang tua semata yang kenyataan di lapangan mereka juga memiliki kesibukan. Seluruh komponen lingkungan pendidikan harus bisa saling bekerja sama demi kelancaran proses pembelajaran seperti yang diutarakan (Malik, 2020) bahwa sekolah dan orang tua harus bekerja sama demi membangun lingkungan belajar anak-anak terutama ketika siswa bergantung pada lingkungan sekolah dan keluarga. Selanjutnya (Rusmiati et al, 2020) dalam artikelnya menyatakan jika keberhasilan pembelajaran daring secara umum ditentukan oleh kesiapan teknologi dukungan dan kolaborasi dari semua pemangku kepentingan, termasuk pemerintah, sekolah, guru, orang tua dan masyarakat.…”
Section: Kendala Kontribusi Pembelajaran Daringunclassified
“…For example, Timmons et al ( 2021 ) found that teachers did not use differentiated instruction to address the needs of individual learners and did not implement inquiry learning pedagogical approaches commonly used in primary grade classrooms. Researchers in India reported that children did not feel connected in online classes, felt distracted, and did not feel comfortable communicating with their teachers through online platforms (Malik & Tyagi, 2020 ).…”
Section: Quality Of Remote Instructionmentioning
confidence: 99%
“…However, school administrators, teachers, and parents hardly had any time for preparing for this transition (Erlam et al, 2021 ). As a result, the process, and outcomes of remote instruction during the pandemic have been widely contested around the world (Malik & Tyagi, 2020 ). Overseeing the teaching and learning process as well as serving as mediators between the home and school, teachers are critical informants who can share their experiences and insights gained during the remote instruction process.…”
mentioning
confidence: 99%